A look at medicalized childhood (Research, Society and Development, 2019)
This article discusses medicalization in childhood and reflects on the possible causes of this phenomenon and its consequences on the subjective constitution of the child. The reflections exposed depart from the place destined to infancy, fruit of the historical, economic and cultural context of the society. Thus, a theoretical and qualitative review of the existing literature was carried out, which dealt with the subject in question, focusing on contemporary Brazilian society. It is observed that the school and the parents, in an attempt to fit the children into the norms of normality established by the society, produce problems that will be treated as demands for health professionals, who abuse the use of Ritalin. Against the use of these substances, nongovernmental organizations and researchers present possible ways in projects with the direct participation of children, as a therapeutic resource not to silence them by the excessive use of medicalization.